Study of Antihypertensive effects of Ocimum sanctum (Bangladesh Journal of Medical Science, 2016)
Background: Ocimum sanctum is a well reputed medicinal herb being used in the treatment of various ailments in this Indo Pak Subcontinents since ancient time.Methods: In this study the Antihypertensive effects of water extract of Ocimum sanctum and Water soluble fraction of methanol extract of Ocimum sanctum were tried for its antihypertensive effects on albino rats. Extracts were administered via vein and BP was recorded in the carotid artery by direct invasive method.Result: Normal blood pressure was 81/71 mm of Hg (mean blood pressure was 75 mm of Hg. Water extract of Ocimum sanctum has got significant antihypertensive effect (19-30 %). Water soluble fraction of methanol extract of Ocimum sanctum has also got significant antihypertensive effect (15-27 %).Bangladesh Journal of Medical Science Vol.15(3) 2016 p.357-361